KEPENTINGAN EKONOMI – POLITIK PAPUA NUGINI DALAM MENERIMA KEBIJAKAN PAPUA NEW GUINEA SOLUTION (PNG SOLUTION) DENGAN AUSTRALIA UNTUK MENGATASI PENCARI SUAKA - Eka Susanti (HI 16 UMY 123, 2016)
*123 This paper is analyzing the political economic interest of Papua New Guinea in receiving PNG Solution in collaboration with Australia to overcome the asylum seeker. This paper explains the reason why Papua New Guinea is willing to be a shelter for the Australia asylum seekers. Based on the fact, Papua New Guinea wants to cooperate with Australia regarding the asylum seekers because Papua New Guinea received help from Australia in several sectors which becomes national interestin Alotau Accord 2012. In addition, this topic also use rational actor model to explain this paper. Keyword: rational actor model, asylum seeker, PNG Solution, Alotau Accord 2012, Regional Resettlement Arrangement